PCR- RFLP analysis (PRA) of non tuberculous mycobacteria (NTM) isolated from animal specimens and environment using hsp65 and rpoB genes - BANNALIKAR, A S; VERMA, RISHENDRA (The Indian Journal of Animal Sciences, 2012)
Non tuberculous mycobacteria (99) comprising 34 isolates from animal specimens, 57 soil and 8 water samples from animal dwellings were identified on the basis of growth rate, pigmentation, colony morphology and biochemical reactions. Of the 8 species recovered from animal specimens 4 (M. fortuitum, M. smegmatis , M. chelonae and M. abscessus) were prevalent in soil while only 2 of these species (M. fortuitum and M. smegmatis) prevailed in water samples. These isolates along with 13 reference strains of mycobacteria were subjected to polymerase chain reaction-restriction fragment length polymorphism analysis (PRA) of hsp65 and rpoB genes. All the isolates generated products of 439 bp and 360 bp in PCR of hsp65 and rpoB genes respectively. Restriction digestion of the product of hsp65 and BstEll and Haelll and that of rpoB with Mspl and Haelll in separate reactions and analysis of digests by agarose gel electrophoresis revealed RFLP patterns characteristic for most of the species tested. Out of the 16-mycobacterial species evaluated, 13 produced a single PRA pattern, while 3 species generated 2 patterns in both the PRA methods. M. abcessus and M. chelonae were distinguishable from each other. M. fortuitum isolates were differentiated into M. fortuitum I and M. fortuitum II, M. avium complex isolates into M. intracellulare and M. avium, M. kansasii isolates into M. kansasii I and M. kansasii V and M. gordonae into M. gordonae II and M. gordonae (new type) by both the methods. Both the PRA methods could not make a distinction between M. tuberculosis and M. bovis however, PRA with hsp65 was found better since it yielded relatively large sized and distinct band.